2018 Computing in Cardiology Conference (CinC) 2018
DOI: 10.22489/cinc.2018.285
|View full text |Cite
|
Sign up to set email alerts
|

Heart Block in the Athlete – Role of Ion Channel Remodelling as Studied Using a One-Dimensional Computational Model of the Atrioventricular Node

Abstract: In swim-trained mice, we previously observed atrioventricular (AV) node dysfunction characterised by first-degree heart block and a prolonged Wenckebach cycle length. Notably, patch clamp recordings from isolated AV node myocytes demonstrated a significant reduction of I f (by ~60%) and I Ca,L (by ~40%) in swimtrained mice as compared to sedentary control mice. The effect of the observed changes in ionic currents was investigated using a one-dimensional computational model of the AV node. This was used in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…On the other hand a slowing of AV-nodal conduction has also been observed in a murine model of inducible cardiac-specific knockout of the pacemaker channel gene Hcn4 [43] implying that HCN channels themselves may be involved in signal conduction through the AV node. This notion is supported by in-silico studies using a theoretical model of AV-nodal conduction [22,23]. Hence, both block of HCN channels and block of voltage-gated sodium channels may contribute to slowing of conduction through the AV node by ivabradine.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand a slowing of AV-nodal conduction has also been observed in a murine model of inducible cardiac-specific knockout of the pacemaker channel gene Hcn4 [43] implying that HCN channels themselves may be involved in signal conduction through the AV node. This notion is supported by in-silico studies using a theoretical model of AV-nodal conduction [22,23]. Hence, both block of HCN channels and block of voltage-gated sodium channels may contribute to slowing of conduction through the AV node by ivabradine.…”
Section: Discussionmentioning
confidence: 84%
“…Hence the exploration of the molecular underpinnings of the effect of ivabradine on AV-nodal conduction may be of substantial clinical relevance [17][18][19][20][21]. Although in silico studies suggest that block of HCN channels per se may result in slowing of AV-nodal conduction [22,23], it has been suggested that this effect of ivabradine Hächl et al: Ivabradine Effects on Human Cardiac Ion Channels may result from additional block of voltage-gated Ca 2+ and/or K + channels [24]. In addition to voltage-gated Ca 2+ channels, voltage-gated Na + channels may also contribute to AV-nodal conduction (see below).…”
Section: Introductionmentioning
confidence: 99%